Lipodystrophy in Human Immunodeficiency Virus (HIV) Patients on Highly Active Antiretroviral Therapy (Haart) - N. Sunil Kumar; J. Shashibhushan; Malappa; K. Venugopal; Huggi Vishwanatha; Mahesh Menon (Journal of Clinical and Diagnostic Research, 2015)
Background: In recent years, abnormal lipid deposition (both lipoatrophy and fat redistribution) and its related complications have changed from an anecdotal issue into a major problem for HIV (Human Immunodeficiency Virus) infected patients on HAART (Highly Active Anti-Retroviral Therapy). Lipoatrophy and fat redistribution are potentially stigmatizing complications of HAART and leads to poor adherence among patients. Hence we conducted this study to determine the pattern and to assess various risk factors for maldeposition of lipids in HIV patients. Materials and Methods: A cross-sectional case series study was conducted in ART PLUS centre, Bellary over a period of 8 months from January to August 2014 in HIV patients on ART to determine risk factors associated with and epidemiological pattern of fat redistribution or atrophy. Results: A total of 50 patients with LD {lipodystrophy} (26 with fat redestribution and 24 with lipoatrophy LA were diagnosed in this period. Most of them belonged to younger age and was commonly seen in females (76%). Patients with LA had a significantly lower BMI (18.73 ± 7.4), {the p-value being 0.19} compared to LH group (21.54 ± 7.62). The duration of disease was comparable among both groups (6.96 years in LH and 5.79 years in LA group) {p-value is 0.29}. There was a relatively good immunity among these patients with mean CD4 count was 509.23 in LH and 545.91 in LA group {single CD4 count was taken and the p-value was 0.001}. Most of the patients were in TLN (Tenofovir, Lamivudine, Nevirapine) regimen (58%). The duration that patient was on ART before commencement of study varied from patient to patient, but the mean duration was approximately five years in fat redistribution group and 4.5 years in LA group. There were no derangements in lipid and sugar levels among them. Conclusion: This study shows the need to identify and impact of LD with respect to treatment adherence in young patients especially female patients. Early community based screening for LD by social workers and targeted annual screening might help early detection and awareness about LD. Also adopting the least toxic regimen is one of the main aspects of LD management.